2016
DOI: 10.2174/1874325001610010512
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Metal-on-metal Hip Arthroplasty with Well Fixed and Positioned Acetabular Component Using a Dual-mobility Head and Review of Literature

Abstract: Background:As a consequence of use of metal-on-metal hip arthroplasties some patients have precised revision for pain or metal hipersensivity reactions among other causes. We propose to salvage monoblock acetabular component and femoral component using a dual-mobility head and perform a lower morbidity operation in young patients preserving host bone stock in cases with well fixed and positioned components.Objective:(1) What clinical problems have been reported in patients with Metal-on-metal hip arthroplastie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(57 reference statements)
0
2
0
2
Order By: Relevance
“…The rationale of leaving the well-fixed acetabular component in situ and converting the implant to a dual mobility is certainly correct and starts from the assumption to reduce intra-and post-operative morbidity and to preserve bone stock, as documented by several reports [12,20,22,25,26]. Nevertheless, the incidence of so many cases of complications for a total of 10.77%, of which 10 (7.6%) of true dislocations and intra-prosthetic dislocations in a such short period of time, requires proper debate and consideration, especially considering that the majority of procedures are off-label practices, therefore unsupported by the Food and Drug Administration, the European International Medical Devices Regulators Forum and manufacturers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale of leaving the well-fixed acetabular component in situ and converting the implant to a dual mobility is certainly correct and starts from the assumption to reduce intra-and post-operative morbidity and to preserve bone stock, as documented by several reports [12,20,22,25,26]. Nevertheless, the incidence of so many cases of complications for a total of 10.77%, of which 10 (7.6%) of true dislocations and intra-prosthetic dislocations in a such short period of time, requires proper debate and consideration, especially considering that the majority of procedures are off-label practices, therefore unsupported by the Food and Drug Administration, the European International Medical Devices Regulators Forum and manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that cup revision in MoM can be technically difficult [13], it is often associated with loss of bone stock and could increase the risk of dislocation when small heads are used for revision surgery [14]. Therefore, it has been proposed to leave in place the acetabular component and to convert the implant into a dual mobility system [13,[15][16][17][18][19][20][21][22][23][24][25][26]. Although dual mobility (DM) bearings offer an easy solution avoiding the intraoperative and time-associated complications related to the removal of a well-fixed and well-positioned acetabular shell, other considerations should be evaluated before this new solution is considered as reliable and reproducible.…”
Section: Introductionmentioning
confidence: 99%
“…Se han publicado casos similares, con buenos resultados. [12][13][14][15][16] Pritchet, cirujano de los EE.UU., presentó 14 casos con 41 meses de seguimiento. No describe revisiones ni ningún tipo de complicaciones.…”
Section: Discussionunclassified
“…Destacan la preservación del stock óseo y la ausencia de complicaciones. 15 Estas copas, como bien se ha descrito en esta revista, poseen una doble articulación. 17 Se usan en Europa desde hace décadas, pero recién, en 2009, fueron aprobadas por la Food and Drug Administration.…”
Section: Discussionunclassified